Investigation of the Optical Arrangement in Radio Telescopes - Yehdish, Makhan Lal (2015)
Radio telescopes are instruments that are widely used by astronomers to study astronomical objects which emit radio waves on the Earth at different wavelengths and frequencies. A radio telescope operates by detecting and receiving the emitted radio waves from the outer space. These radio waves are converted into radio frequency (RF) signals and they are sent to the radio receiver for further processing before their information are stored into the computer and recording devices. A radio telescope basically consists of reflector system, feed system, RF transmission line and a radio receiver. Both the reflector system and feed system are the two elements that form the optical arrangement in the radio telescope. The arrangement of these optical elements has a great impact on the performance of radio telescope. Therefore, the performance of the radio telescope was analyzed by varying the size and focal length of the reflector system. This was done by inserting the desired values for the required parameters into the simulation software to design the geometry of the frontfeed reflector system. The designed geometry was simulated to generate its radiation pattern for performance evaluation. Overall, the results show that the performance of single reflector feed system can be maximized either by increasing the size or decreasing the focal length of the reflector. In addition, the performance of dual reflector feed system can be improved by trading off both aperture blockage and diffraction loss. Among the 2 different reflector feed system, the single reflector feed system provides the best performance in terms of having a lowest side lobe level Unlike the dual reflector feed system, its mechanical design is much simpler and thus, only a lower construction cost needed.